Pengaruh Konseling dan Alat Bantu Pengingat Pengobatan terhadap Kepatuhan Minum Obat dan Outcome Klinik Pasien Diabetes Melitus dan Hipertensi - Much Ilham Novalisa Aji Wibowo; Didik Setiawan; Nindya Dwi Ikhwaniati; Fitria Amalia Sukma (Fakultas Farmasi Universitas Pancasila, 2020)
The World Health Organization declares Diabetes Mellitus and Hypertension as one of the health emergencies. Adherence to medication is an important factor in controlling this disease. Research is needed to find out the combination of counseling and treatment reminder aids will aff ect adherence and clinical outcomes. Pretest-posttest design was conducted in February 2019 - May 2019. Sample population was Prolanis patients at Puskesmas Kembaran I, Purwokerto Timur II and Sumbang I. The inclusion criteria were 66 patients with type 2 diabetes and 72 patients with hypertension. The determination of the pretest-posttest group was by simple random sampling. The adherence instrument used MARS, counseling and medication reminder tools according to pharmaceutical counseling guidelines. The respondents were women, low education, normal BMI, didn’t work, combination of Diabetes medication and single medication for Hypertension. The pretest group was categorized as non-adherent, but experienced an increase after the intervention. The interventions given also had an eff ect on improving medication adherence and controlling the clinical outcome of type 2 DM patients and hypertensive patients at the Puskesmas (p-value 0,000 <0.05). The combination of pharmacist counseling interventions with medication reminders is more eff ective in increasing medication adherence in patients with type 2 Diabetes mellitus and Hypertension.